GAP ANALYSIS PENERAPAN SAK ETAP PADA PENYUSUNAN LAPORAN KEUANGAN UKM DI KABUPATEN KUDUS (Studi pada UKM Padurenan Jaya) - Rizqi Senoaji, Aditya; Cahyonowati, Nur (Diponegoro Journal of Management, 2014)
This study aims to determine the analysis SAK ETAP application of accounting standards to SMEs in Kudus, understanding the application of SAK ETAP in the manufacture of SME financial statements, and the government knows socialization Kudus to SMEs on the use of SAK ETAP in making its financial statements. This is done because the presence of SAK ETAP is expected to help SMEs to develop good financial report. This study used a qualitative method with a case study approach. Analysis of the application of SAK ETAP in the Holy City can be identified by the case study approach. The results of this study show that the application of SAK ETAP at SME businesses in the Holy City has been undertaken by SMEs business although in practice there are less appropriate for modeling the process of its financial statements. This occurs because SMEs do not have the human resources who are competent in financial reporting.